Velkoplošné systémy vytápění a chlazení - Kohlová, Vendula (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Cílem diplomové práce je navrhnout vytápění a chlazení v administrativní budově a předváděcí hale. Teoretická část se zabývá velkoplošnými systémy vytápění a chlazení. Jsou zde popsány druhy těchto systémů a jejich výhody a nevýhody. Praktická část je věnována návrhu vytápění a chlazení v zadané administrativní budově a předváděcí hale. V této části jsou řešeny dvě varianty návrhu. První varianta uvažuje použití tepelného čerpadla jako zdroje tepla a chladu. Ve druhé variantě řešení je použit jako zdroj tepla plynový kondenzační kotel a jako zdroj chladu chiller. Experimentální část se zabývá měřením vlastností jednoho stropního panelu. Hlavním úkolem bylo stanovení chladicího výkonu stropního panelu.

The aim of the diploma thesis is to design heating and cooling in the office building and the showroom. The theoretical part deals with large-scale heating and cooling systems. The types of these systems and their advantages and disadvantages are described here. The practical part is devoted to the design of heating and cooling in the assigned office building and the showroom. In this part, two variants of the design are considered. The first variant considers the use of a heat pump as a source of heat and cold. In the second variant of the solution, a gas condensing boiler is used as a heat source and a chiller as a cold source. The experimental part deals with measuring the properties of one ceiling panel. The main task was to determine the cooling capacity of the ceiling panel.
Large-area heating and cooling systems
Keywords: Tepelné čerpadlo; plynový kondenzační kotel; chiller; podlahové vytápění; fancoily; chladicí stropní panely; administrativní budova; předváděcí hala.; Heat pump; gas condensing boiler; chiller; underfloor heating; fan coils; cooling ceiling panels; office building; showroom.